Meningkatkan Harga dan Kualitas Pelayanan untuk Memaksimalkan Keputusan Pembelian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The rise and fall of retail store sales indicates unstable consumer purchasing decisions. There are two main factors that can influence purchasing decisions at retail stores, namely price and service quality. From the research results, it is hoped that we can find out the influence of price and service quality on purchasing decisions at the Happy Shop which is located in Singakerta Village, Ubud District, Gianyar Regency. The population in this study is infinitive or not known for certain. The sample size determined was 75 Happy Shop consumers using the accidental sampling method. The data analysis technique used is multiple linear regression. The results of the partial significance analysis prove that price and service quality together have a positive and significant effect on purchasing decisions. The suggestions given include, among other things, regarding price, namely selling products using a bundling and cross selling system. Regarding service quality, it is recommended to provide training to employees and establish standard operational procedures.